Le trop proche ? Mariages dans le nom du père à Paris aux xvie et xviie siècles - Robert Descimon (L'Atelier du CRH)
In the 16th and 17th centuries, Parisians sometimes married a homonymous relative. These alliances did not seem to be a taboo, they undoubtedly participated in the cycles of alliances and replicated alliances with distant relatives which constituted one of the components of modern kinship. The article analyses the context of a number of such alliances in the paternal name to present the hypothesis that they are, like fidéicommis, attempts to concentrate the constituent elements of lineages (property and dignity) whose fragility was felt more in a context of crisis of the transmission of social domination.